Menerokai kefahaman kreativiti dalam kalangan pemimpin di sektor perbankan - Nurhasniza, Binti Abdul Razak (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study aims to explore the understanding of creativity among the leaders in banking sector through the definition ofcreativity given, the identification elements or characteristics that are practiced in the form of creativity, the method used to foster creativity in organizations. creativity and contribution to the achievement of individuals and organizations. A total informant in this study is 5 persons which consist of employee from private sector in the banking sector. There are 3 banking organizations that participated in this study. Data were collected through interviews and audio recordings that have been recorded. The results ofthis study indicate that employees in positions ofresponsibility in the banking sector have a deep level of understanding of creativity. In fact, the results indicate any answers given by the informant must be associated with an organizational environment. This clearly shows that creativity plays an important role in every organization in the promotion ofnew ideas that lead to changesfor the better.